2017
DOI: 10.1111/avsc.12309
|View full text |Cite
|
Sign up to set email alerts
|

Experiment‐based recommendations for biodiversity‐friendly management of mountain hay meadows

Abstract: Question: The biodiversity of mountain hay meadows has historically been maintained through traditional, low-intensity farming practices. In recent decades, however, agricultural intensification for hay production has led to dramatic declines in their biodiversity. This study asks: which management practices can contribute to maintaining the biodiversity value of mountain hay meadows without jeopardizing agricultural revenue?Location: Eleven semi-natural meadows, canton of Valais, inner Alps, southwest Switzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Intensification induces a rapid impoverishment of the flora of montane and subalpine meadows in the short term (Andrey et al, 2014) and mid-term (Boch et al, 2021;Lessard-Therrien et al, 2017), as demonstrated by our earlier work within the same experimental set up and corroborated in this study. In addition, effects of intensification are more pronounced in species-rich grasslands (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Intensification induces a rapid impoverishment of the flora of montane and subalpine meadows in the short term (Andrey et al, 2014) and mid-term (Boch et al, 2021;Lessard-Therrien et al, 2017), as demonstrated by our earlier work within the same experimental set up and corroborated in this study. In addition, effects of intensification are more pronounced in species-rich grasslands (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The treatment plots received low, medium or high inputs, corresponding to a combination of aerial irrigation (sprinklers) and fertilization (slurry) that mimicked a gradient of intensification, with, respectively, 1/3 (low intensity; I + F 1/3), 2/3 (mid intensity; I + F 2/3) and 3/3 (high intensity; I + F 3/3) of the quantity of inputs that would be necessary to achieve the maximum local hay yield in a given meadow according to its agronomic properties. The exact amount of slurry applied per plot are presented in Table S2, and in Andrey et al (2014, 2016) and Lessard‐Therrien et al (2017). Mowing regimes had to be adapted to phytomass production to simulate local farming practice: C‐ and I + F 1/3 plots were mown once a year, the other plots twice a year (see Andrey et al, 2014, 2016; Lessard‐Therrien et al, 2017 for details).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the outcomes of plant responses to water supply increase may reflect experimental design. All studies focussing on precipitation increases were conducted in situ where increased precipitation was typically applied to experimental plots using sprinklers [51,52] or by diverting rainfall from passive rainout shelters [53]. Studies rarely reported soil moisture at varying depths, yet these methods of water application potentially only recharge the surface soil layers.…”
Section: Increases In Water Supplymentioning
confidence: 99%
“…The first dataset (called the observational dataset, henceforth) contains observational data on bryophyte species richness along a land-use intensity gradient in German grasslands (the German Biodiversity Exploratories; Fischer et al, 2010). The second dataset (called the experimental dataset, henceforth) contains experimental data on bryophyte species richness from a replicated field experiment that tested the effects of modern fertilization and irrigation upon plant and invertebrate communities of Swiss mountain hay meadows, with the objective to define optimal trade-offs for sustainable grassland management (e.g., Andrey et al, 2016;Lessard-Therrien et al, 2017). Combining these two datasets therefore allowed us to generalize findings across a range of different grassland types and to assess i) how intensification of land-use components affects bryophyte species richness and ii) how important direct intensification effects on bryophyte species richness are, compared to plant biomass-mediated indirect ones (see details below).…”
Section: Study Sites Land Use and Vegetationmentioning
confidence: 99%